Foreign aid and corruptionin selectedafricanmuslimcountries: an empirical study based on autoregressive distributed lag (ardl) model - Adewale, Abideen Adeyemi (Technology Institute of Daadab, Kenya, 2013)

(untitled)
Considering the dismal growth performance in many African countries despite the huge transfer of resources as foreign aid or development assistance (DA) by various multilateral development and financial institutions like OECD, USAID and Islamic Development Bank (IDB) among others; itwas not surprising that Transparency International through its Corruption Perceptions Index (CPI)reports classified most African countries as icons of corruption. In this connection therefore, this study makes an attempt to empirically investigate the nature and pattern of causal relationship existing between corruption and foreign aid in selected African Muslim Countries (AMCs) like Morocco, Egypt, Tunisia and Senegal who are among the major recipients of the development assistance of IDB in more than three decades. As a matter of fact, Autoregressive Distributed Lag (ARDL) model based on Cointegration and Granger-causality tests was adopted. Basically, the findings from our study indicate that the nature of causality existing between corruption and foreign aid is both in the short and long-run analysis. Also, the pattern of causality is both unidirectional and bidirectional. Importantly, our findings revealed the relevance of the corruption trap hypothesis of Collier (2006) to all the countries in the sample, especially for Morocco. Stemming from these findings, we recommend that IDB and other African development partners like the OIC, OECD, OPEC and a host of others should give more commitment to the enthronement of good governance. They should especially facilitate the international war against corruption in these countries and Africa at large because these two measures are fundamental to the growth and development process of the continent.